THU0461 Rebound-Associated Vertebral Fractures after Denosumab Discontinuation: A Series of 8 Women with 35 Spontaneous Vertebral Fractures. (15th July 2016) - Aubry Rozier, B.; Stoll, D.; Gonzalez Rodriguez, E.; Hans, D.; Lamy, O.
Abstract : Background: Osteoporosis (OP) treatments are given for a limited period of time because of a risk/benefice balance. Reversibility of OP treatment is observed by the measurements of bone markers turnover (BMTs) and bone mineral density (BMD). The effect on vertebral fracture (VFx) is difficult to evaluate. The OP treatment discontinuation is associated with an increase of BMTs and a more or less rapid decrease of BMD. Denosumab (Dmab) discontinuation is associated with a severe rebound effect on BTMs and BMD for near 24 months. A recent publication suggests an increase of VFx [1]. Methods: We report the cases of 8 postmenopausal women. They received Dmab 60mg every 6 months for 2 to 8 doses. The 8 women were on calcium and vitamin D. A wide biological assessment excluded a secondary cause of OP. VFx were documented by MRI. Results: Five OP women without any prior fragility fracture were treated every 6 months with 4 to 6 Dmab doses. Dmab was stopped because there was no more OP on BMD (3 women 55, 56 and 59 y old), the aromatase inhibitors were stopped (77y old) and according to the wish of the patient (77y old). 9 to 16 months after Dmab discontinuation, they presented respectively 5 (D11, D12, L2-L4), 7 (D9, D12-L5), 2 (D11 and D12), 3 (D12-L2) and 9 (D5-D9 and D11-L2) symptomatic spontaneous (SS) VFx. A 65 y old woman with osteoporosis and 3 prevalent VFx was treated every 6 months with 8 Dmab doses. Ten months after Dmab discontinuation she presented 2 SSVFx (D12, L3). These 62 y old woman (osteopenia, treated with aromatase inhibitors) received 2 Dmab doses every 6 months. The subsequent Dmab dose was forgotten. Twelve months after the last Dmab dose she presented a D10 SSFx. A 71 y old woman (one prevalent VFx and one hip fracture) received 2 Dmab doses with a delay of 11 months because of a lack of compliance. Eleven months after the last Dmab dose she presented 5 SSVFx (D12, L2-L5). Conclusions: These 8 cases show a severe increased risk of vertebral fractures in the 9 to 16 months after the last injection of Dmab. The occurrence of these fractures can be explained by the severe rebound effect observed after denosumab discontinuation. It is urgent to: 1) inform the health authorities and patients of this risk; 2) determine treatment regimens before or at the time of denosumab discontinuation. References: Aubry-Rozier B, Gonzalez-Rodriguez E, Stoll D, Lamy O. Severe vertebral fractures after denosumab discontinuation: 3 cases reports. Osteoporos Int. 2015 Oct 28. Disclosure of Interest: None declared